Deadly Choices empowering Indigenous Australians through social networking sites. (5th April 2017) - McPhail-Bell, Karen; Appo, Nathan; Haymes, Alana; Bond, Chelsea; Brough, Mark; Fredericks, Bronwyn
Summary: The potential for health promotion through social networking sites (SNSs) is widely recognized. However, while health promotion prides itself in focusing on the social determinants of health, its partiality for persuading individuals to comply with health behaviours dominates the way health promotion utilizes SNSs. This paper contributes to an understanding of collaborative ways SNSs can work for health promotion agendas of self-determination and empowerment in an Indigenous Australia context. An ethnographic study was undertaken with Deadly Choices, an Indigenous-led health promotion initiative. The study involved participant observation of interactions on Deadly Choices SNSs between Deadly Choices and its online community members. Deadly Choices provides an example of SNSs providing a powerful tool to create a safe, inclusive and positive space for Indigenous people and communities to profile their healthy choices, according to Indigenous notions of health and identity. The study found five principles that underpin Deadly Choices' use of SNSs for health promotion. These are: create a dialogue; build community online and offline; incentivise healthy online engagement; celebrate Indigenous identity and culture; and prioritize partnerships. Deadly Choices SNSs empowers Indigenous people and communities to be health promoters themselves, which represents a power shift from health promotion practitioner to Indigenous people and communities and more broadly, an enactment of Indigenous self-determination on SNSs. Mainstream health promotion can learn from Indigenous health promotion practice regarding the use of SNSs for health promotion agendas.